An investigation on the surface austempering of ductile cast iron - Fayyaz, Abdolali; Varahram, Nasser; Davami, Parviz (Penerbit Universiti Kebangsaan Malaysia, 2017)
This research presents surface austempering of ductile cast iron. Surface of pearlitic ductile cast iron samples were austenitised and heated to 810 and 850°C and held at these temperatures for 90 and 105 sec and then austempered at a temperature of 325°C for 60 and 90 min. The microstructure of samples was evaluated by optical microscopy. The hardness profile in polished cross section was also determined. In addition, the depth of austmpered layer was measured. The result indicated that temperature and time of austenitisation intensely effect on surface austempering process. The test results also revealed that the hardness of austempered layer increase when the austenitising temperature and time increase. After surface austempering of ductile cast iron samples, the highest hardness achieved 450 HV in austempered surface-layer. The highest depth of austempered layer 1.7 mm was obtained.